2021
DOI: 10.3389/fphar.2021.657287
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pharmacogenetics of CYP2D6 in Chinese Children: Loratadine as a Substrate Drug

Abstract: Objective: The elucidation of CYP2D6 developmental pharmacogenetics in children has improved, however, these findings have been largely limited to studies of Caucasian children. Given the clear differences in CYP2D6 pharmacogenetic profiles in people of different ancestries, there remains an unmet need to better understand the developmental pharmacogenetics in populations of different ancestries. We sought to use loratadine as a substrate drug to evaluate the effects of ontogeny and pharmacogenetics on the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Maturation rates are difficult to generalize, and enzyme-specific information needs to be determined for an accurate estimate of drug metabolism including clinical conditions such as sepsis and complex surgery, nutritional state and diet (infant formula versus breast milk), polymorphism and even antenatal exposure to cigarette smoke ( Czekaj et al, 2005 ; Blake et al, 2006 ; Allegaert, 2017 ; Li et al, 2021 ).…”
Section: Drug Disposition In Premature Neonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturation rates are difficult to generalize, and enzyme-specific information needs to be determined for an accurate estimate of drug metabolism including clinical conditions such as sepsis and complex surgery, nutritional state and diet (infant formula versus breast milk), polymorphism and even antenatal exposure to cigarette smoke ( Czekaj et al, 2005 ; Blake et al, 2006 ; Allegaert, 2017 ; Li et al, 2021 ).…”
Section: Drug Disposition In Premature Neonatesmentioning
confidence: 99%
“…In vivo CYP2D6 metabolism has been investigated in premature neonates using tramadol as substrate ( Allegaert et al, 2008a ; 2008b ). Here, PMA and CYP2D6 polymorphisms ( Li et al, 2021 ) was found to determine the O-demethylation activity in the preterm neonates.…”
Section: Exploring the Available Data On Premature Neonates: An Examp...mentioning
confidence: 99%